2009
DOI: 10.1088/0004-6256/137/4/3788
|View full text |Cite
|
Sign up to set email alerts
|

Probing Star Formation at Low Metallicity: The Radio Emission of Super Star Clusters in SBS 0335–052

Abstract: We present high-resolution radio-continuum observations of the nascent starburst in the metal-poor galaxy SBS 0335−052. These radio data were taken with the Very Large Array and include observations at 0.7 cm, 1.3 cm, 2 cm, 3.6 cm, and 6 cm. These observations enable us to probe the thermal radio nebulae associated with the extremely young star-forming regions in this galaxy. Two discrete and luminous star-forming regions are detected in the south of the galaxy that appear to be associated with massive star cl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
83
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(91 citation statements)
references
References 87 publications
8
83
0
Order By: Relevance
“…Free-free emission at 870 μm in SBS 0335−052 870 μm emission can contain contributions from different physical processes: cool dust, thermal free-free emission (or bremsstrahlung) from ionized gas, and synchrotron emission from supernova remnants and their diffused non-thermal emission after longer timescales. In SBS 0335−052, synchrotron emission contributes a significant fraction of the total at long cm wavelengths and low spatial resolution (Hunt et al 2004), but not at the highest radio frequencies observed (43 GHz, Johnson et al 2009). Extrapolating from the 1.3 cm flux of ∼0.52 mJy (Hunt et al 2004;Johnson et al 2009), we estimate a free-free flux at 870 μm of 0.40 ± 0.07 mJy.…”
Section: Alma Observationsmentioning
confidence: 95%
See 1 more Smart Citation
“…Free-free emission at 870 μm in SBS 0335−052 870 μm emission can contain contributions from different physical processes: cool dust, thermal free-free emission (or bremsstrahlung) from ionized gas, and synchrotron emission from supernova remnants and their diffused non-thermal emission after longer timescales. In SBS 0335−052, synchrotron emission contributes a significant fraction of the total at long cm wavelengths and low spatial resolution (Hunt et al 2004), but not at the highest radio frequencies observed (43 GHz, Johnson et al 2009). Extrapolating from the 1.3 cm flux of ∼0.52 mJy (Hunt et al 2004;Johnson et al 2009), we estimate a free-free flux at 870 μm of 0.40 ± 0.07 mJy.…”
Section: Alma Observationsmentioning
confidence: 95%
“…2, we present the data we have acquired and compiled in order to better constrain the dust mass and gas content in SBS 0335−052. We then estimate the free-free contribution to Izotov et al (1999); (3) Reines et al (2008); (4) Johnson et al (2009);(5) in the entire SBS 0335−052 E region (Ekta et al 2009); (6) Thuan & Izotov (1997a).…”
Section: Constraining Cool Dust In Sbs0335−052mentioning
confidence: 99%
“…Thus, the authors were able to estimate the size D of the emitting region by fitting a Gaussian, and from the observed flux, determine the EM, and infer the rms electron density n e . In other cases (NGC 4214, NGC 1741, Mrk 8, Mrk 33, VII Zw 19, Pox 4, Tol 35, Mrk 1236NGC 6946, NGC 253, M 33: Johnson et al 2001;SBS 0335-052: Hunt et al 2004;Johnson et al 2009), the spatial resolution is insufficient to resolve the regions. Then the radio spectrum can be fit by models of homogeneous, isothermal, dust-free, ionization bounded regions of ionized gas, to obtain the turnover frequency ν t , the EM, n e , and infer the size D of the region (e.g., Deeg et al 1993;Johnson et al 2001;Hunt et al 2004).…”
Section: Extragalactic Radio Data Setsmentioning
confidence: 99%
“…In fact, ultra-dense H ii regions or radio "supernebulae" have been proposed as SSC progenitors, observed in their very young embedded state (Kobulnicky & Johnson 1999;Johnson et al 2003;Johnson et al 2009). This would be consistent with our finding that extreme conditions are necessary to explain the radio sample.…”
Section: "Active" and "Passive" Bcdsmentioning
confidence: 99%
“…T72 denotes galaxies that were observed, but not detected, by Tovmassian (1972) at 9.5 mm (31.6 GHz). T94 (Turner & Ho 1994), B00 (Beck et al 2000), B02 (Beck et al 2002), B03 (Beswick et al 2003), C04 (Chyży & Beck 2004), J04 (Johnson et al 2004), L04 (Lisenfeld et al 2004), R05 (Rosa-González 2005), T06 (Tsai et al 2006), B07 (Beck et al 2007), R08 (Reines et al 2008), J09 (Johnson et al 2009), D11 (Dumas et al 2011), K11 (Kodilkar et al 2011), and A11 (Aversa et al 2011) denote galaxies that were observed at lower frequencies. The galaxies are described in more detail in these papers.…”
Section: Introductionmentioning
confidence: 99%